Verbal Learning and Memory Impairment in Children with Fetal Alcohol Spectrum Disorders - O’Leary, Catherine E. (Alcohol Clin Exp Res, 2015)
BACKGROUND: Previous studies using the California Verbal Learning Test-Children’s Version (CVLT-C) to examine effects of heavy prenatal alcohol exposure on verbal learning and memory have reported impaired information acquisition (i.e., encoding), rather than retrieval, as the primary mechanism underlying learning and memory impairment. We administered the CVLT-C to two independent cohorts to determine whether (1) effects on encoding are also seen at moderate exposure levels, using both categorical (diagnostic/exposure group) and continuous exposure measures; (2) these deficits are specific or secondary to alcohol-related impairment in IQ; and (3) effects on retrieval can be detected over and above effects on initial encoding. METHODS: We administered the CVLT-C and Wechsler Intelligence Scale for Children to 151 Cape Town heavy and nonexposed children (M=10.3 years), and 291 Detroit adolescents recruited to over-represent moderate-to-heavy prenatal alcohol exposure (M=14.4 years). RESULTS: Effects on encoding in the heavily exposed Cape Town cohort and on retrieval in both cohorts were significant after adjustment for IQ. Although effects on retrieval were no longer significant in Cape Town after control for initial encoding, effects on recognition memory continued to be evident in Detroit. Children with full or partial fetal alcohol syndrome were less able to use the semantic cluster encoding strategy implict in the CVLT-C. CONCLUSIONS: Effects on verbal learning were seen primarily in the more heavily exposed Cape Town cohort; effects on recall and recognition memory were also seen at moderate exposure levels in Detroit. These effects were not attributable to alcohol-related impairment in overall intellectual competence. The finding that effects on retention continued to be evident after statistical adjustment for initial encoding in Detroit suggests that a fetal alcohol-related deficit in retrieval is not secondary to a failure to encode the initial information. These data confirm that this impairment in initial learning is mediated, in part, by failure to use the semantic cluster learning strategy.